Towards identifying potent new hits for glioblastoma. Issue 11 (9th October 2018) - Sherer, Chris; Prabhu, Saurabh; Adams, David; Hayes, Joseph; Rowther, Farzana; Tolaymat, Ibrahim; Warr, Tracy; Snape, Timothy J.
Abstract : Scaffolds have been identified which provide promising platforms for future development of chemotherapeutic agents against resistant glioblastoma subtypes. Abstract : Glioblastoma is a devastating disease of the brain and is the most common malignant primary brain tumour in adults. The prognosis for patients is very poor with median time of survival after diagnosis measured in months, due in part to the tumours being highly aggressive and often resistant to chemotherapies. Alongside the ongoing research to identify key factors involved in tumour progression in glioblastoma, medicinal chemistry approaches must also be used in order to rapidly establish new and better treatments for brain tumour patients. Using a computational similarity search of the ZINC database, alongside traditional analogue design by medicinal chemistry intuition to improve the breadth of chemical space under consideration, six new hit compounds (14, 16, 18, 19, 20 and22 ) were identified possessing low micromolar activity against both established cell lines (U87MG and U251MG) and patient-derived cell cultures (IN1472, IN1528 and IN1760). Each of these scaffolds provides a new platform for future development of a new therapy in this area, with particular promise shown against glioblastoma subtypes that are resistant to conventional chemotherapeutic agents.